Healthcare institutions do not favor care. Meaning of humanized care for people directly participating in it (2014)
ABSTRACT: This study sought to understand the meaning of humanized care for those directly participating in it. Methodology.This was qualitative research with phenomenological interpretative approach conducted in Medellín, Colombia, during 2013. It included 16 participants among nurses, adult patients, and relatives. To gather the information, in-depth interviews were used;data analysis was performed manually according to the scheme proposed by Cohen, Kahn, and Stevees. Results. According tothe participants, institutions do not favor humanized care due tothe inaccessibility of services whose possible causes are, among others, excessive procedural red tape, lack of resources, and long waits. Additionally, they state that nurses’ work overload keeps them away from the patients and prevents caring for them.Conclusion. For the participants in the study, the humanized care practice of humanized care is affected negatively, on one side, by the service offered by healthcare institutions; and, on the other,by the influence exerted upon nurses, which conditions, in turn,how care is delivered.